The legacy of the occupation-Japan - Passin, Herbert (Occasional Papers of the East Asian Institute, 1968)
This publication is sponsored by the Japan Foreign Relation Project, which was organized in 1960 under the aegis of the Institute to support advanced graduate work, the holding of international conferences, promotion of research and publication by specialists, and translation of important works by foreign scholars.